Structural investigation and functional on 50kDa protein from Salmonella enterica serovar Typhi. - Choong, Yee Siew
The typhoid fever incident rate is as high as 1100 cases per 100,000 population in developing and under developed countries. Thus, the research on typhoid fever has prompt to the development ofaffordable and accessible typhoid diagnostic to replace the conventional Widal test.